Radiologic Efficacy and Patient Satisfaction after Minimally Invasive Unilateral Laminotomy and Bilateral Decompression in Patients with Lumbar Spinal Stenosis: A Retrospective Analysis - Kim, Seung-Kook; Ryu, Sungmo; Kim, Eun-Sang; Lee, Sun-Ho; Lee, Su-Chan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims Lumbar spinal stenosis (LSS) is the most common spinal disease in older adults. Although surgical modalities are recommended in patients who are unresponsive to conservative treatment, the most appropriate minimally invasive surgical procedure for patients with LSS remains controversial. Moreover, few previous studies have focused on patient-centered outcomes with radiologic correlation. In the present study, we aimed to investigate radiologic efficacy and patient satisfaction following bilateral decompression via unilateral laminotomy.Materials and Methods We performed a retrospective analysis of radiologic efficacy and patient satisfaction in a series of surgical patients treated at our institution. We classified patients into two groups based on the primary pathology (i.e., central or lateral recess stenosis). Medical records were analyzed retrospectively for radiologic outcomes and clinical parameters including pain and changes in quality of life. Data related to outcomes were collected at 2 weeks, 3 months, and 12 months after surgery in the outpatient clinic.Results Among the 122 patients enrolled in this study, 51 had central spinal stenosis; 71 had lateral recess stenosis. Radiologically, we observed significant improvements in the anteroposterior diameter and cross-sectional area of the dural sac (central stenosis) and the lateral width of the central canal and depth of the lateral recess (lateral recess stenosis). Two weeks and 12 months after the surgical procedure, we observed significant improvements in the extent of symptoms, patient satisfaction, and quality of life (including physical function).Conclusion Our findings suggest that bilateral decompression via a unilateral approach shows improved radiologic outcomes, varying based on the type of stenosis. Furthermore, patient satisfaction significantly improved regardless of the type of disease.
Keywords: spinal stenosis; decompressive laminectomy; minimally invasive spinal surgery; unilateral laminotomy and bilateral decompression